On Didactic Poetry. The Criterion of Purpose as the Principle of Generic Classification in Polish Classicistic Poetics - Markowska-Fulara, Helena (Zagadnienia Rodzajów Literackich, 2019)
The article is dedicated to the category of purpose as a criterion for distinguishing literary types and kinds in early 19th-century Polish poetics. The author discusses this topic on the basis of treatises (by E. Słowacki, J.F. Królikowski, and J. Korzeniowski) which apply a two-tier division of poetry into types and genres. She analyses three issues: distinguishing didactic poetry as a type of literature; the general criteria for literary typology; and the distinction between poetry and rhetoric. As a point of reference, the author refers to the claims and ideas of S. Skwarczyńska, whose diagnosis concerning the ‘popular poetics’ of the period between the two world wars confirms the durability of classicistic genological categories. Paper presented as a part of Project no 2017/27/N/HS2/00395 “In Search of the Language. The Birth of Polish Literary Studies in the Context of European Ideological Changes (1795–1830)” funded by the National Science Centre, Poland.